Bright green fluorescence of Asian paper wasp nests. Issue 181 (25th August 2021) - Daney de Marcillac, Willy; Nguyen, Lien Thi Phuong; Aracheloff, Camille; Berthier, Serge; Schöllhorn, Bernd
Abstract : An exceptionally bright fluorescent biomatter was discovered when exploring, with UV-A light, the nests of several oriental paper wasp species of the genus Polistes, a genus of diurnal social insects. Fluorescence spectra of the cocoon cap membranes revealed narrow emission bands in the green range of the visible spectrum. Large Stokes shifts of around 160 nm and high fluorescence quantum yields of up to 35% were measured. Transmission spectra were recorded in order to estimate the contribution of the fluorescence to the visible light transmitted through the cocoon cap membrane. The nest fluorescence of the Vietnamese wasps was compared with a European and an American species. Potential biological functions of these interesting fluorescence properties of the studied biomaterial are discussed. The discovery of this striking example of a fluorescent terrestrial biomaterial may contribute to the debate on adaptive biological functions of natural fluorescence and falls in line with the growing interest in biodiversity and bio-inspiration.